المرأة الجزائرية والتنشئة الاجتماعية في سياق التغير الاجتماعي - قديري, الأستاذ: مصطفى (Sciences de l'Homme et de la Société, 2016)
اليومية وتسارع وتيرة التنافس لتحسين أوضاعهم الاقتصادية والاجتماعية، ما نتج عنه تغير في الأدوار وتنشئة الأفراد الثقافية والاجتماعية نرى أن له علاقة ببعض الظواهر الباثولوجية لم تكن موجودة قبلاً، فخروج المرأة للعمل من أجل الحياة زاد في ارتفاع نسب العنف ضدها كذلك تغير أنماط تنشئة هذه المرأة على أدوار نراها جديدة مقارنة بما مضى. إننا نرى هنا أن لكل ذلك علاقة بالتغير الاقتصادي والاجتماعي للمجتمع الجزائري خلال العقدين الأخيرين (1990-2010) علاقة تبرز من خلال تزايد وجود المرأة في الفضاء العام ومشاركتها للرجل في كثير من الوظائف والأدوار وحتى نستطيع استقراء نوع تلك العلاقة طرحنا سؤالاً عامًا: هل هناك علاقة بين التغير الاقتصادي والاجتماعي وظاهرة العنف ضد المرأة في المجتمع الجزائري؟      Abstract :              Through this article, we tried to surround the social pressing that is done on the individuals in the society due to social life, their willingness to do better, and their daily life sacrifice which results a such individuality and what sociocultural changes the society knows because of the economics regimes established by the states and their impacts on the persons, especially their behavioural aspects, and as a result, the sociopathologic phenomenon which did never exist before. The most noteworthy thing is the fact that the woman goes out to find a job in the objective of saving her life and to insure a good family life. On the other hand, the principals that would protect the woman are decreasing; among them is what the family offers to protect the woman's social life. This may have a link with the changes of the socioeconomic state in the Algerian society during the two last decade’s 1990-2010, what helps us, thru the woman's need to go out for a job and her participation in a plenty activities next to the man, to know the relevancies and their effect on the her in and out her family, and the violence that she may undergo. We tried to ask a general question: Is there a link between the socioeconomic change in Algeria and the violence against the woman?